Involving user perspective in a software risk management process. Issue 12 (6th November 2015) - Lindholm, Christin
Abstract: More and more user groups are using medical devices. Heart starters are, for example, available in public places and used by non‐professionals. Different mobile medical applications, designed to help people manage their own health, are now being added to the medical device spectra. Users handling medical devices make errors, but by involving users in the risk management process, it is possible to lower the risk of these errors. This paper presents an evaluation of the value of complementing a traditional risk management process with an emphasised user perspective. A medical device software risk management framework is being designed, and the risk management process should be regarded as the first part of the framework. The main goal of the evaluated risk management process is to integrate users and user perspective into the risk management process. The results indicate that the use of use cases as input at risk meetings makes the discussions more focused, saving effort and time. When users attend the risk meetings, user perspective and domain knowledge are brought into the process, affecting risk identification and risk assessment. The results also show that the use of usability testing gives valuable input to the risk management process. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The goal of the evaluated risk management process is to integrate user perspective into the risk management process. The results indicate that the use of use cases as input at risk meetings makes the discussions more focused, saving effort and time. When users attend the risk meetings, user perspective and domain knowledge are brought into the process, affecting risk identification and risk assessment. The results show that the use of usability testing gives valuable input to the risk management process.